PROFIL HUBUNGAN SOSIAL PESERTA DIDIK YANG HOBI MEMBACA NOVEL DI SMA NEGERI 9 PADANG - Sari, Reno - (Bimbingan dan Konseling, 2014)
Background of this research was because fanatic hobby of students that is reading thenovel which making their social relationship doesnât grow as well because less communication andinteraction with their friends at school. The purpose of this research is to observe as far as readingthe novel influence students social relationship at SMAN 9 Padang. Focus on this research isstudents social relationship who are hobby reading the novel with their same gender friends andwith their opposite gender friends.This research uses descriptive qualitative approach whichdescribing indications, facts, and reality about students social relationship. Informan for thisresearch are: students, close friends of students, counselor, and subject teacher. Instrument for thisresearch was interview guide, technique for processing data through data reduction, datapresentation, and then pulling conclusion.Result of this research found that student socialrelationship doesnât grow like usual, although it is with their same gender friends and also withtheir opposite gender friends. This caused by fanatic hobby reading the novel by students. Interestin reading the novel make student less communication and interaction with their friends. Base onthis research, recommendad for students, counselor, and relevant parties to cope fanatic hobbyreading the novel by students.